Exploring the frontier: nonlinear optics in low dimensional materials - Adeshina Mohammad A.; Kim Hyunmin (Nanophotonics)
Nonlinear optics, the study of intense light–matter interactions, traditionally uses bulk materials like LiNbO3 for device fabrication. However, these materials face challenges such as limited nonlinear susceptibility, large dimensions, and phase matching issues, limiting compact and integrated devices. Recent research has illuminated that a variety of low-dimensional materials exhibit markedly stronger nonlinear optical responses than their bulk counterparts. This has made nonlinear optics in low-dimensional materials a dynamic area of study, allowing for rapid light–matter interactions and advancing nonlinear nanophotonic and optoelectronic applications. These applications span diverse areas, from wavelength conversion and the generation of ultrashort laser pulses to advancements in quantum photonics and integrated photonic technologies. This review covers two-dimensional materials such as graphene and transition metal dichalcogenides to one-dimensional forms like carbon nanotubes and nanowires, and further to zero-dimensional structures including nanoparticles and quantum dots. By providing a comprehensive overview of the current state of non-linear optics in the context of low-dimensional materials, this review not only encapsulates the existing knowledge base but also charts a course for future explorations in this rapidly progressing domain.